Rising tiger : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2022)
America's top spy, Scot Harvath, with democracy itself hanging in the balance, is thrust into a completely unfamiliar culture where he can trust no one as he fights to take down the country's most powerful enemy--and for his life.